Kemampuan Berpikir Kritis Siswa MTs Ditinjau dari Multiple Intelligences Melalui Model Pembelajaran Peer Led Guided Inquiry - Siti Fatimah; Mayang Sari (Musamus University, 2022)
The purpose of this research is to describe in detail the critical thinking skills of its students in terms of students' multiple intelligences through the PLGI (Peer Led Guied Inquiry) learning model. The indicators used are adopted from Facione which includes interpreting, analyzing, evaluating, and inferring. The type of research used is qualitative with a descriptive approach. The instruments in this study include multiple intelligences test questionnaires, KBK 1 and 2 test questions, and interview guidelines. The research subjects were taken from the results of the MI test questionnaire which consisted of four research subjects representing each type of intelligence which included logical-mathematical, linguistic, visual-spatial, and intrapersonal intelligence. After that, KBK 1 and 2 tests were given and interviews were conducted with research subjects. Checking the validity of the data using time triangulation, and data analysis include reducing data, presenting data, and drawing conclusions. From the results of the study, unique facts were found which showed that the critical thinking abilities of students with logical-mathematical intelligence and students with visual-spatial intelligence have in common, namely being able to meet only two indicators so that their critical thinking abilities lie at a fairly critical level. Then students with linguistic intelligence can meet three indicators so that their critical thinking skills lie at a critical level. Meanwhile, students with intrapersonal intelligence can fulfill all critical thinking indicators, so their critical thinking skills lie at a very critical level.